1980
DOI: 10.1080/23808985.1980.11923823
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Teacher Communication Style, Trait and State Communication Apprehension and Teacher Effectiveness

Abstract: The empirical model tested in this stUdvexamined the effects of teacher communication stvle (TCS) on students' affect and behavioral commitment in collel!e classes. Additionally, the model posited a mediational function for teachers' and st~dents' trait and state communication apprehension for perceptions of teacher style and teacher effectiveness. Multiple regression and commonality analyses indicated that only student perceptions of all three dimensions of TCS were related to teacher effectiveness. Students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…From this perspective teachers engage in behaviors (e.g., nonverbal immediacy, affinity-seeking) that aid in the development and maintenance of relationships with their students. Prior researchers have found that relational behaviors are related directly to students' ratings of their teachers as well as their own motivation and affective and cognitive learning (Frymier, 1994;Gorham & Christophel, 1990;Kearney & McCroskey, 1981;Kelley & Gorham, 1988;Plax, Kearney, McCroskey, & Richmond, 1986;Richmond, 1990;Roach & Byrne, 2001). The next first-order construct is student characteristics.…”
Section: Definitions Of Constructsmentioning
confidence: 96%
“…From this perspective teachers engage in behaviors (e.g., nonverbal immediacy, affinity-seeking) that aid in the development and maintenance of relationships with their students. Prior researchers have found that relational behaviors are related directly to students' ratings of their teachers as well as their own motivation and affective and cognitive learning (Frymier, 1994;Gorham & Christophel, 1990;Kearney & McCroskey, 1981;Kelley & Gorham, 1988;Plax, Kearney, McCroskey, & Richmond, 1986;Richmond, 1990;Roach & Byrne, 2001). The next first-order construct is student characteristics.…”
Section: Definitions Of Constructsmentioning
confidence: 96%
“…JACR AUGUST 2000 We believed that our first hypothesis was more likely to be supported on the responsiveness dimension than on the assertiveness dimension, even though responsiveness appears to be more genetically driven than assertiveness. First, in work reported by Kearney and McCroskey (1980) it was found that responsiveness and versatility (flexibility) were substantially correlated. Since a certain degree of versatility would need to be present for our first hypothesis to be correct in any case, it would be most likely that it would be correct for responsiveness.…”
Section: Sco and Scsmentioning
confidence: 96%
“…Classroom CA has most often been associated with low course satisfaction (Scott & Wheeless, 1975), low cognitive performance (Bouris & Allen, 1992), higher drop-out rates (McCroskey, Booth-Butterfield, & Payne, 1989), women's learning style preferences (Dwyer, 1998), and perceptions of learning (Allen, Long, O'Mara, & Judd, 2008). While research on CA and student learning typically focused on receiver disruptions, studies also examined CA characteristics in college teachers (Kearney & McCroskey, 1981), primary and secondary teachers (McCroskey, Andersen, Richmond, & Wheeless, 1981), and teaching assistants (Roach, 1998). Thus, CA provided a process bridging source-receiver content, execution, and reception that complicated the linear view of instruction.…”
Section: Receiver Characteristicsmentioning
confidence: 97%